The efficacy of Lactobacillus acidophilus and rhamnosus in the reduction of bacterial load of Helicobacter pylori and modification of gut microbiota—a double‐blind, placebo‐controlled, randomized trial - Chen, Mei‐Jyh; Chen, Chieh‐Chang; Huang, Yu‐Chun; Tseng, Chieh‐Chih; Hsu, Jing‐Ting; Lin, Yi‐Fen; Fang, Yu‐Jen; Wu, Ming‐Shiang; Liou, Jyh‐Ming (Helicobacter (Cambridge, Mass.), 2021)
Background Probiotics may alter the gut microbiota and may reduce antibiotic‐related dysbiosis after H. pylori eradication. However, whether probiotics are effective in reducing the bacterial load of H. pylori and modifying the gut microbiota remains unknown. We aimed to assess the efficacy of Lactobacillus acidophilus and Lactobacillus rhamnosus in reducing the bacterial load of H. pylori and modifying the gut microbiota. Materials and methods In this double‐blind, randomized, placebo‐controlled trial, we recruited 40 adult subjects with moderate to high bacterial loads of H. pylori, defined as a mean delta over baseline (DOB) value of the 13C‐urea breath test (13C‐UBT) of 10 or greater every 4 days 6 times. Eligible subjects were randomized in a 1:1 ratio to receive either probiotics containing Lactobacillus acidophilus and Lactobacillus rhamnosus or placebo twice daily for 4 weeks. 13C‐UBT was measured weekly from the beginning of treatment to 2 weeks after treatment. Amplification of the V3 and V4 hypervariable regions of the 16S rRNA was performed for fecal microbiota. Results A total of 40 subjects were randomized to receive probiotics or placebo. The DOB value was significantly lower in the probiotic group than in the placebo group after 4 weeks of treatment (26.0 vs. 18.5, p = .045). The DOB value was significantly reduced compared to that at baseline in the probiotic group (18.5 vs. 26.7, p = .001) but not in the placebo group (26.0 vs. 25.0, p = .648). However, the eradication rate for H. pylori was 0% in both groups. There was no significant difference in the DOB values between the two groups 1 and 2 weeks after discontinuation of the probiotics. There were also no significant changes observed in the α‐diversity and β‐diversity at week 4 compared to baseline in the probiotic group (p = .77 and 0.91) and the placebo group (p = .26 and 0.67). Conclusions Although the use of Lactobacillus acidophilus and Lactobacillus rhamnosus may reduce the bacterial load of H. pylori, there were no significant changes in the composition of gut microbiota. This trial is registered with ClinicalTrials.gov, NCT02725138.